Media Compensation in Utilizing Video Conference for Brainstorming: Kendelite Creative Case Study - Gita Ayu Maharani; Atikah Silvia; Afifah Dwiandini (Green Publisher Indonesia, 2024)
Brainstorming is a broadly used approach across various fields, including the creative industry, to facilitate the process of ideation. As technology advances, video conference is often used to facilitate virtual brainstorming, particularly in the creative field of advertising agencies. The media compensation theory (Hantula et al., 2011) was used as a tool to investigate the use of media in the brainstorming process in order to examine how video conferencing facilitates brainstorming activities within the production division of advertising agencies. Data was collected via interview and direct observation during the brainstorming process. The findings suggest that video conference facilitates the brainstorming process by two main categories of utilization: technological utilization and communicative utilization. Moreover, it was discovered that videoconferencing is not able to facilitate brainstorming for a long period of time as it causes fatigue for team members and cannot fully replace face-to-face communication in the brainstorming process. This study supports the adaptation aspect of media compensation theory within the context of brainstorming in advertising agencies.